2022
DOI: 10.1002/bmc.5335
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and gas chromatographic method for the determination of profenofos residues in/on green pea and cucumber

Abstract: Herein we report a novel, accurate and cost-effective gas chromatography method for the determination of average deposits of profenofos on green pea and cucumber following good agricultural practices. Additionally the risk assessment, dissipation and waiting period for profenofos were determined. The average initial deposits (2 h after spraying) of profenofos in/on green pea and cucumber were 3.41 and 3.62 mg kg À1 respectively following two applications at a 10 day interval of profenofos 50EC formulation. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
(24 reference statements)
2
9
0
Order By: Relevance
“…To our knowledge, no report to date is available regarding the method validation and simultaneous quantification of xanthones, flavonoids and steroids by HPLC. In continuation of our previous communication (Ahmad Dar et al, 2020; Dangroo et al, 2016; Dar et al, 2014, 2015, 2016, 2018, 2019; Fayaz et al, 2018; Singh et al, 2018; Wani et al, 2019a, 2019b, 2022), we herein report for the first time method development and simultaneous quantification of isolated natural products 1–11 (Figure 1) from Codonopsis ovata by HPLC. Various validation aspects of the analysis such as linearity, specificity, recovery, precision, robustness, limit of detection (LOD) and limit of quantification (LOQ) have been determined.…”
Section: Introductionsupporting
confidence: 81%
“…To our knowledge, no report to date is available regarding the method validation and simultaneous quantification of xanthones, flavonoids and steroids by HPLC. In continuation of our previous communication (Ahmad Dar et al, 2020; Dangroo et al, 2016; Dar et al, 2014, 2015, 2016, 2018, 2019; Fayaz et al, 2018; Singh et al, 2018; Wani et al, 2019a, 2019b, 2022), we herein report for the first time method development and simultaneous quantification of isolated natural products 1–11 (Figure 1) from Codonopsis ovata by HPLC. Various validation aspects of the analysis such as linearity, specificity, recovery, precision, robustness, limit of detection (LOD) and limit of quantification (LOQ) have been determined.…”
Section: Introductionsupporting
confidence: 81%
“…The average per capita daily consumption of vegetables in India is 200 g (Anonymous, 2012), of which the proportion of green chilies in the daily diet is a maximum of 5% (10 g day −1 ). Therefore, the TMRC has been calculated by multiplying the residue level with the daily consumption of chili (Jan et al, 2018, 2022; Wani et al, 2022; Wani, Dar, et al, 2019; Wani, Jan, et al, 2019). During the experimental period, the TMRC values were found to be 0.01212 and 0.01207 mg person −1 day −1 and 0.01953 and 0.01948 mg person −1 day −1 for maximum and average spiromesifen residues at the recommended dose (96 g. a.i.…”
Section: Resultsmentioning
confidence: 99%
“…An intensive literature review revealed that numerous methods, like UV spectrophotometry, gas chromatography–mass spectrometry (GC–MS), high‐performance liquid chromatography (HPLC) and high performance thin liquid chromatography, can be employed for the quantification of cypermethrin from natural sources, but such methods are either tedious or lack sensitivity and specificity and are expensive. However, GC appears to be the method of choice, affording the separation and quantification of insecticides (Wani et al, 2022). Its simplicity, ecofriendly and cost‐effectiveness are the advantages of using GC instead of other techniques for the quantification of pesticides from natural sources.…”
Section: Introductionmentioning
confidence: 99%